Variations in Daily Maximum Areas and Longitudinal Widths of Solar Coronal Holes in 2017-2020 - Riehokainen Alexandr; Smirnova Victoria; Solov'ev Alexander; Tlatov Andrey; Zhivanovich Ivan; Al-Hamadani Firas; Strekalova Polina (MDPI, 2022)
We considered coronal holes as a manifestation of the large-scale magnetic field of the Sun. The main goal of this work was to study the variations in the largest areas and longitudinal widths of solar coronal holes observed daily in the polar and mid-latitude zones on a time scale of 984 days. Statistical methods of fast Fourier transform (FFT), wavelet transform, and empirical mode decomposition (EMD) were used to detect periodicity in the variations of the considered parameters. Long-term variations in the daily measured areas and longitudinal widths of the largest solar coronal holes with periods of 8-9,13-15, and 26-29 days were detected in three zones of the Sun: polar (north and south) and equatorial. The obtained periods are most clearly visible at the equatorial zone. In the polar zones the period of 8-9 days has a weak amplitude. We interpreted variations with periods of 8-9,13-15, and 26-29 days as a rotation of the six-, four-, and two-sector structure of the large-scale solar magnetic field.